Mobile learning and education: synthesis of Open Access research - Cardoso, Teresa (2018)
In a global and mobile society characterized by the possibility of portability, mobile devices are no longer accessories, but they are rather resources that we cannot do without. In fact, nowadays no one seems willing to give up these tools recognizing its potential in various fields. For instance, they allow not only to shorten various distances but also to respond to different situations of our daily life, and also, of course, they provide moments of leisure and entertainment. Thus, combining all these attributes and to benefit from them in education seems obvious. However, to what extent and how are mobile devices integrated in education? Is mobile learning or m-learning a reality? Or a fiction, instead? Therefore, the present study aims at clarifying these issues through a literature synthesis of research available in online databases. In this state of the art, m-learning is briefly characterized, namely, by describing some of its particular types and environments and also by a SWOT analysis. Students and teachers’ perceptions and practices on m-learning were also identified. We further identified determining factors that both students and teachers consider important in the use of mobile devices and in the acceptance of mobile learning. In short, the systematization of the analyzed literature summarizes experiences that promoted changes in both the alphabetization and digital literacy of the whole participating school communities. One can conclude that m-learning is a research area with a recent past, a dynamic present, and a promising future.